Preparation of Magnesium-zinc Alloy by Mechanical Alloying - Fousova, Michaela; Capek, Jaroslav; Vojtech, Dalibor (Manufacturing Technology Journal, 2014)
Mechanical alloying is one of the ways how to prepare nanostructured and amorphous metallic materials. In this paper we used this method to prepare Mg-Zn alloy containing 50 wt.% of zinc. Powders produced by milling in a planetary ball mill were consequently compacted by the SPS method, a very fast method which prevents grain coarsening. The prepared samples were subjected to a closer examination - microstructure, phase composition, hardness and short-term thermal stability were studied. We found out that the prepared powder consisted of Mg and Mg7Zn3 phases, which were very fine and homogeneously distributed. After the SPS compacting, the metastable Mg7Zn3 phase decomposed and new phases (Mg, MgZn, MgZn2, Mg2Zn11) formed. The compacted sample possessed relatively inhomogeneous microstructure and hardness about 260 HV5. Investigation of the short-term thermal stability was accomplished by annealing at temperatures up to 300 °C. We observed changes in hardness - it regularly decreased up to 200 °C and then it slightly increased.
Keywords: Mg-Zn alloy; mechanical alloying; SPS